2022
DOI: 10.3390/healthcare10010125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Home-Based Tele-Pilates Intervention on Pregnant Women: A Pilot Study

Abstract: Pilates is effective for training the core muscles and stabilizing the hip joints, which provides relief from pelvic pain and low back pain during pregnancy. However, there are no specific guidelines on appropriate physical exercises for pregnant women due to the current pandemic. We aimed to apply the exercise standard proposed by the American College of Obstetricians and Gynecologists to home-based tele-Pilates exercise (HTPE), to determine its effect on the physical and mental health of pregnant women. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…In addition, a systematic review and meta-analysis of RCTs conducted among pregnant women revealed that sleep quality was improved among exercise group participants when determined by the PSQI [ 36 ]. Like our findings, an RCT of an 8-week supervised home tele-based Pilates program 50 min twice a week ( n = 7) and control ( n = 7) during pregnancy showed that PSQI global scores were significantly lower in the intervention compared to the control group [ 37 ]. In contrast to our findings, an RCT among Danish pregnant women with or at high risk of depression found no difference in the global PSQI score after 12 weeks of supervised group exercise (70 min twice a week) starting from GA 17–22 weeks [ 35 ].…”
Section: Discussionsupporting
confidence: 79%
“…In addition, a systematic review and meta-analysis of RCTs conducted among pregnant women revealed that sleep quality was improved among exercise group participants when determined by the PSQI [ 36 ]. Like our findings, an RCT of an 8-week supervised home tele-based Pilates program 50 min twice a week ( n = 7) and control ( n = 7) during pregnancy showed that PSQI global scores were significantly lower in the intervention compared to the control group [ 37 ]. In contrast to our findings, an RCT among Danish pregnant women with or at high risk of depression found no difference in the global PSQI score after 12 weeks of supervised group exercise (70 min twice a week) starting from GA 17–22 weeks [ 35 ].…”
Section: Discussionsupporting
confidence: 79%
“…Yoga and Pilates may be particularly useful exercise types. Recent pilot studies in pregnant women have shown that a 7-week yoga intervention during the second trimester improved sleep disturbances,55 8 sessions of yoga over 2 weeks improved sleep quality,56 and 8 weeks of home-based Pilates improved sleep quality 57. More work is warranted to better understand the relationship between exercise frequency, intensity, type, and time with sleep in pregnancy, and studies utilizing objective measures of sleep and exercise, which provide more precise information about these parameters, are critically needed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, future investigations should compare sleep patterns in pregnancy, and after childbirth and perinatal depression. Further studies are also necessary to understand the efficiency of exercise programs specialized for postpartum women who may be vulnerable to depression, since exercises such as Pilates improve the quality of sleep in pregnant women [ 24 ]. Women undergoing treatment for insomnia during the third trimester of pregnancy reported less symptomatology of postpartum depression than those who did not receive treatment, thus suggesting a link between sleep quality during pregnancy and perinatal depression [ 25 ].…”
Section: Discussionmentioning
confidence: 99%